Implementasi Dakwah Digital Instagram @premarriagetalk Dalam Membentuk Keluarga Sakinah - Khasanah, Rosa Maulida; Ayu Faiza Algifahmy (IQTIDA : Journal of Da'wah and Communication, 2024)
A sakinah marriage is a dream for everyone. Some experts reveal that the reason for many divorces is due to the ineffective implementation of Premarital Guidance. Premarital Guidance has the aim of creating a sakinah family as stated in QS. Ar-Rum: 21. This study aims to dissect the use of Instagram @premarriagetalk as a digital da'wah media in the formation of a sakinah family Indonesia is the 4th highest Instagram user as the most active user in the world, so this is the background of Instagram as the object of research. And the @premarriagetalk Instagram account is used as a digital da'wah media, especially about the formation of a sakinah family through a premarital guidance program. The author's research method is qualitative with a content analysis approach. The data validity test uses triangulation techniques while for data analysis techniques using the Miles and Huberman model analysis technique, among others; data collection, data display, verification and conclusions. Based on research that has been conducted on the @premarriagetalk account, it shows that the content presented through is designed aesthethic, eyecathing, timeless, adjusts the needs of followers and is also packaged in reels with illustrations. The @premarriagetalk account presents information and education on how to form a sakinah family which is shared, namely by having sincere intentions, facilitating the process towards marriage, paying attention to the state of the heart, carrying out a contract, and holding a walimah according to Islamic teachings.